Mdm2 gene amplification is associated with luminal breast cancer progression in humanized PDX mice and a worse outcome of estrogen receptor positive disease. Issue 8 (28th December 2021) - Wege, Anja Kathrin; Rom‐Jurek, Eva‐Maria; Jank, Paul; Denkert, Carsten; Ugocsai, Peter; Solbach, Christine; Blohmer, Jens‐Uwe; Sinn, Bruno; van Mackelenbergh, Marion; Möbus, Volker; Trumpp, Andreas; Marangoni, Elisabetta; et al.
Abstract: Estrogen receptor‐positive breast cancer is a highly prevalent but heterogeneous disease among women. Advanced molecular stratification is required to enable individually most efficient treatments based on relevant prognostic and predictive biomarkers. First objective of our study was the hypothesis‐driven discovery of biomarkers involved in tumor progression upon xenotransplantation of Luminal breast cancer into humanized mice. The second objective was the marker validation and correlation with the clinical outcome of Luminal breast cancer disease within the GeparTrio trial. An elevated mdm2 gene copy number was associated with enhanced tumor growth and lung metastasis in humanized tumor mice. The viability, proliferation and migration capacity of inherently mdm2 positive breast cancer cells in vitro were significantly reduced upon mdm2 knockdown or anti‐mdm2 targeting. An mdm2 gain significantly correlated with a worse DFS and OS of Luminal breast cancer patients, albeit it was also associated with an enhanced preoperative pathological response rate. We provide evidence for an enhanced Luminal breast cancer stratification based on mdm2 . Moreover, mdm2 can potentially be utilized as a therapeutic target in the Luminal subtype. Abstract : What's new? Breast cancer is extremely heterogeneous, even within subtypes. For best outcomes, therapies must be tailored to the molecular profile of the particular tumor. Here, the authors searched for new biomarkers in ER‐positive breast cancer using a humanized tumor mouse (HTM) model, which replicates a functional human immune system. They discovered that amplification of a gene, mdm2, was associated with tumor progression. Treatment with agents that inhibit mdm2 slowed down cell proliferation, viability and migration of cancer cells in vitro. Clinical testing for mdm2 status could help improve targeted treatment for these patients.